IAPSM’s Position Paper on Influenza Vaccines for Adult Immunization in India - Nikita Sharma; Madhur Verma; Kapil Goel; Muralidhar M. Kulkarni; Anu Bhardwaj; Sahil Sharma; Tejbeer Singh; Madhu Gupta; Anuradha Nadda; Lalit R. Sankhe (Indian Journal of Community Medicine)
Influenza causes significant morbidity, hospitalizations, and mortality due to lower respiratory tract infections in India. This paper reviews the current evidence regarding influenza epidemiology, the need for vaccination, immunogenicity, and efficacy of available vaccines and provides recommendations for influenza vaccination for adults by the Indian Association of Preventive and Social Medicine (IAPSM). The risk group among adults includes people with chronic disease, the elderly, immunocompromised individuals, pregnant women, travelers, and healthcare workers. Influenza activity is affected by seasons, humidity, and latitude, leading to variability in influenza peaks in different regions of India. The most effective preventive intervention against influenza is vaccination. Current influenza vaccines have good safety profiles, vaccine efficacy, and acceptable cost-effectiveness. As the virus mutates, the vaccine composition should follow WHO recommendations for the current influenza season. Introducing readily available, conventional, and less expensive trivalent influenza vaccines under the national program can achieve maximum impact on the adult population and potentially prevent future outbreaks and pandemics. IAPSM recommends considering routine use of IIV for all individuals above 60 years, adults with comorbidities, and pregnant women in India. The program managers should consider the pattern of influenza seasonality in a particular region. Influenza surveillance conducted through a structured network of laboratories in India has the potential to provide information about circulating strains, morbidity, and mortality. IAPSM emphasizes conducting community-based studies regarding influenza’s burden, vaccine efficacy, timing of vaccination, and cost-effectiveness among Indian adults to generate evidence.